THE RELATIONSHIP BETWEEN PERSONALITY, ACADEMIC SELF-EFFICACY, AND ACADEMIC RESILIENCE AMONG 4PS BENEFICIARIES - Shekinah C. Reyes (LP2M Universitas Bina Mandiri Gorontalo, 2023)
As it has profoundly altered practically everyone’s lives, the COVID-19 pandemic has caused tremendous stress throughout the world. The education sector is one of the hardest hits by the pandemic. It has been emphasized that the adverse effects of the pandemic have similarly impacted the education sector worldwide. Resilience has been a crucial factor in facing such adversity as resilience is the ability to bounce back from stressful situations. Similar to resiliency, self-efficacy is situation-dependent and vital in dealing with adversities as self-efficacy has been one’s ability to achieve under certain conditions. Furthermore, personality may affect both resilience and self-efficacy as inherent traits may affect one’s ability to cope with challenges. The present study investigated the role of personality in fostering academic resilience, and the role of academic self-efficacy between the relationship. The three variables were contextualized in the academic setting during the pandemic. The particular interest of the study is students from disadvantaged background due to prominent disparity between those who can and cannot afford the educational transition posed by the pandemic. Using regression and mediation analysis, the results revealed that both personality and academic self-efficacy have significant effect on academic resilience. Academic self-efficacy mediated the relationship between personality and academic resilience; therefore, personality directly and indirectly related to academic resilience through academic self-efficacy. The study recommends to develop and establish a program that will foster specific personality traits, such as openness to experience, conscientiousness, extraversion, agreeableness, and neuroticism.